Taṭwīr ʾAdawāt Ikhtibār Taʿlīm al-Ṣarf al-Muʿtamidah ʿalá Niẓām ʾAndrūyd: Dirāsah Taṭbīqīyah ʿalá Ṭalābat Maʿhad Dār al-Najāh al-ʾIslāmī - Silviya, Arina (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2024)
Technological advancements have become vital in enhancing Arabic language education, particularly in assessing Arabic morphology learning at the Pondok Pesantren Daarun Najaah, where traditional methods lack innovation. This study develops